IMPLEMENTASI WEB SEMANTIK PADA PENCARIAN BUKU PERPUSTAKAAN UIN ALAUDDIN MAKASSAR - Nur Afif - (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
Semantic Web is a set of technologies, which allows the computer to understand the meaning of information based on metadata, which is information about information. The semantic web is a vision of Tim Berners-Lee to make the web a meaningful resource data. This can be realized by using the infrastructure that is defined by the working group at the W3C (World Wide Web Consortium), the Resource Description Framework (RDF). RDF consists of three compositions, namely the subject, predicate and object. Subject and object is an entity which is indicated by the text. While the title is a composition that explains the point of view that will be the subject described by other objects. So that the object or entries can be clearly explained and detailed, and in accordance with the wishes of users who give feedback. College libraries generally have to manage a collection of local (institutional repository) each such book, thesis, journals, research reports produced academic faculty. No exception in the Public Library of UIN Alauddin Makassar. However, from the observation of the researcher, the dissemination of information regarding the collection at the library not optimally managed, so that can lead to delays in the distribution of information regarding the collection to the public library. Implementing a searching tool that implement semantic web technology for the library, is one of solution that can be use to overcome such problem.